2007
DOI: 10.1007/s12028-007-0015-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in intracranial pressure associated with chest physiotherapy

Abstract: Introduction Management of intracranial hypertension is pivotal in the care of brain-injured patients. Summary of Case We report the case of a patient with both a closed head injury and anoxic encephalopathy, who subsequently experienced episodes of refractory intracranial hypertension. The patient's care was complicated by the development of a pneumonia, which required frequent turning of the patient and chest physiotherapy. Conventional wisdom suggests that these interventions may stimulate the patient and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16][17] In contrast, administration of oral care by using either manual or electric toothbrushes among intubated neurologically impaired patients does not result in significant increases in ICP. 18,19 Similarly, Olson et al, in a series of 3 articles, 5,20,21 explored the effects of chest percussion therapy on ICP, finding that such therapy does not adversely affect ICP and may be associated with lower ICP for some patients. Although these interventions are often necessary to provide adequate care for critically ill patients, as they reduce risk of ventilatorassociated pneumonia and pressure ulcers, other nursing interventions are performed with the aim of specifically decreasing ICP values.…”
Section: Review Of Literaturementioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17] In contrast, administration of oral care by using either manual or electric toothbrushes among intubated neurologically impaired patients does not result in significant increases in ICP. 18,19 Similarly, Olson et al, in a series of 3 articles, 5,20,21 explored the effects of chest percussion therapy on ICP, finding that such therapy does not adversely affect ICP and may be associated with lower ICP for some patients. Although these interventions are often necessary to provide adequate care for critically ill patients, as they reduce risk of ventilatorassociated pneumonia and pressure ulcers, other nursing interventions are performed with the aim of specifically decreasing ICP values.…”
Section: Review Of Literaturementioning
confidence: 99%
“…This study was designed to test the null hypothesis (chest percussion does not alter ICP) and to determine the safety of chest percussion when chest percussion was randomly assigned at a specific time of day. An earlier single-subject study 30 indicated a decrease in mean ICP during several episodes of chest percussion. The concept of chest percussion as a means of reducing ICP warrants further investigation.…”
Section: Discussionmentioning
confidence: 93%
“…Other types of auditory stimuli, including audio-taped recordings of messages and various sounds, however, have not been shown to produce significant increases in ICP (Johnson et al, 1989;Schinner et al, 1995;Treloar et al, 1991;Walker et al, 1998). The few studies on chest physiotherapy (Olson et al, 2007;Olson DM, 2009), a source of physical stimulation, have shown that this treatment does not significantly increase ICP. The studies described above demonstrate that the response to a presumed noxious stimulus is highly variable and the effect of oral care cannot be predicted from them.…”
Section: Nursing Interventions and Intracranial Pressurementioning
confidence: 99%